Initial growth of Brachiaria subquadripara (Trin.) Hitchc. plants under different nutritional conditions - Domingos, Vanessa David; Martins, Dagoberto [UNESP]; Costa, Neumarcio Villanova da; Costa, Andreia Cristina Peres Rodrigues da; Marchi, Sidnei Roberto de (FapUNIFESP (SciELO), 2015)
The objective of this study was to evaluate the initial growth of emergent plants of Brachiaria subquadripara under different conditions of availability levels of the nutrients nitrogen (N), phosphorus (P), and potassium (K) provided to the plants via nutrient solution in a greenhouse. The treatments consisted of five concentrations of N (0, 42.0, 84.0, 126.0, and 168.0 mg L-1), five concentrations of P (0, 6.2, 12.4, 18.6, and 24.8 mg L-1) and five concentrations of K (0, 46.8, 93.6, 140.4, and 187.2 mg L-1) which were adapted from a base solution. The results showed that the initial growth of plants was slow up to 21 days after transplantation (DAT) and it increased in accordance with increments in N, P, and K concentrations in the nutrient solution up to the end of the study (35 DAT). The Relative Growth Rate and the Net Assimilation Rate of the B. subquadripara plants were larger when the N, P, and K concentrations were of 84.0, 18.6, and 46.8 mg L-1, respectively. These results suggest that this species can develop in environments considered hypereutrophic.

Propôs-se, neste trabalho, avaliar o crescimento inicial emergindo Brachiaria subquadripara em diferentes condições de disponibilidade dos nutrientes nitrogênio (N), fósforo (P) e potássio (K) via solução nutritiva em casa-de-vegetação. Os tratamentos se constituíram de cinco doses de N (0, 42,0, 84,0 126,0 e 168,0 mg L-1), cinco doses de P (0, 6,2, 12,4, 18,6 e 24,8 mg L-1) e cinco doses de K (0, 46,8, 93,6, 140,4 e 187,2 mg L-1) adaptadas a solução base. Os resultados demonstraram que o crescimento inicial das plantas foi lento até os 21 dias após o transplante (DAT) e crescente de acordo com os aumentos das concentrações de N, P e K em solução nutritiva até o final do experimento (35 DAT). A Taxa de Crescimento Relativo e a Taxa de Assimilação Líquida da B. subquadripara foram maiores nas concentrações de 84,0, 18,6 e 46,8 mg L-1 de N, P e K, respectivamente. Esses resultados sugerem que esta espécie pode se desenvolver em ambientes considerados hipereutróficos.
Crescimento inicial de Brachiaria subquadripara (Trin.) Hitchc. em diferentes condições nutricionais
Keywords: Urochloa subquadripara; Urochloa arrecta; Aquatic plant; Weed; Eutrophication; Water reservoir; Urochloa subquadripara; Urochloa arrecta; Planta aquática; Planta daninha; Eutrofização; Reservatórios hidrelétricos